Treatment of Latent Tuberculosis Infection - Vernon, Andrew (Seminars in Respiratory and Critical Care Medicine, 2013)
Latent tuberculosis infection (LTBI) refers to a circumstance in which viable Mycobacterium tuberculosis (MTB) bacilli are present in an individual but symptoms and signs of active disease are lacking, and the bacilli are relatively inactive metabolically. In favorable circumstances, some of these inactive bacilli resume greater metabolic activity and replication, leading to the development of active tuberculosis disease. Treatment of this condition (TLTBI) is designed to prevent (soon, or in the distant future) this progression from asymptomatic infection to symptomatic, potentially lethal, active disease. This narrative review draws upon recent reviews of LTBI and seeks particularly to include recently published or presented data that are not included in those prior reviews. Adverse effects of treatment are considered, as are the special circumstances of human immunodeficiency virus–related LTBI, drug resistance, and use of TLTBI in the context of tumor necrosis factor alpha (TNF-α) inhibition. The review describes the main studies underpinning Centers for Disease Control and Prevention recommendations on use of the new 3-month isoniazid-rifapentine regimen and points to evolving data that may support future modification of those recommendations.
Keywords: latent TB; TB preventive therapy; TB prophylaxis; isoniazid; 3HP; rifapentine